Creative black & white : digital photography tips & techniques - Davis, Harold , 1953- (Wiley Publishing, 2010)
In the digital age, presenting a photo in black and white is an intentional aesthetic and creative choice. In this visual guide, renowned photographer Harold Davis introduces you to the fascinating world of black and white photography. Using many of his own stunning monochromatic images to illustrate, Davis walks you through the visual ideas that work well with black and white. He shares the technical approaches that you can use to create high quality monochromatic photos.--[book cover]